Euro interest rate swap yields: A GARCH analysis Tanweer Akram (Citibank) and Khawaja Mamun (Sacred Heart University (SHU)) - Tanweer Akram; Khawaja Abdullah al Mamun (Levy Economics Institute of Bard College, 2023)
This paper models the month-over-month change in euro-denominated (EUR) long-term interest rate swap yields. It shows that the change in the short-term interest rate has an economically and statistically significant effect on the change in EUR swap yields of different maturity tenors, after controlling for various macroeconomic and financial variables, such as the month-overmonth change in inflation or core inflation and the growth of industrial production, and the percentage change in the equity price index, the exchange rate, and the size of the European Central Bank's (ECB) balance sheet. It uses a generalized autoregressive conditional heteroskedasticity (GARCH) approach to model the dynamics of the monthly change in EUR swap yields and their volatility. The results of the estimated models of EUR swap yields of different maturity tenors extend the Keynesian view that the central bank's monetary policy actions have a decisive influence on long-term government bond yields and long-term market interest rates, primarily through their effects on the current short-term interest rate.
Keywords: E43; E50; E60; G10; G12; 330; Euro Swaps; Interest Rate Swaps; Short-Term Interest Rate; Monetary Policy; European Central Bank (ECB); Generalized Autoregressive Conditional Heteroskedasticity (GARCH)